Yoghurt feeding inhibits promotion and progression of experimental colorectal cancer - de Moreno, Maria Alejandra (2004)
Background: In BALB/c mice, a yogurt diet given before and after the carcinogen 1, 2 dymethylhydrazine (DMH) inhibited colon cancer. This paper studied at which stage of tumor development (initiation, promotion or progression) yogurt exerts its antitumor activity. Material/Methods: Six experimental groups were used: 1) non-treatment control; 2) DMH control; 3) yogurt- DMH-yogurt: yogurt administered before and after DMH. 4) yogurt-DMH: yogurt given only 10 days before DMH; 5) DMH-yogurt: yogurt given cyclically after DMH; and 6) yogurt control. The groups DMH-yogurt and yogurt-DMH were compared histologically and TNFα, INFγ, IL-10 and IL-4 cytokines, CD4[sup]+[/sup]/CD25[sup]+[/sup] T cells, and apoptotic cells were determined in large intestine biopsies. TNFα and INFγ were also determined in cells isolated from large intestine nodules and from Peyer’s patches. Results: The DMH-yogurt group did not develop tumor. The yogurt-DMH group showed only tumor delay; TNFα, INFγ and IL-10 increasing in this group in all the periods assayed. These results agree with those already reported for DMH control and yogurt-DMH-yogurt. There was no correlation between the high levels of IL-10 and CD4[sup]+[/sup]/CD25+ T regulatory population. IL-4 and apoptotic cells increased in the yogurt-DMH group only in the first months. In the DMHyogurt group, cellular apoptosis increased during the whole treatment. Yogurt feeding induced TNFα and INFγ increases in cells isolated from large intestine nodules. These cytokines also increased in cells from Peyer’s patches of the yogurt control group. Conclusions: These results show that yogurt inhibited tumor progression and promotion by modulating the immune response and stimulating cellular apoptosis.